Creation Of Legal Basis Of Trade Union Organizations In Ferghana Valley (Texas Journal of Multidisciplinary Studies, 2025)
This article describes the processes of reforming the trade union system and the essence of effective solutions to the obstacles that are a source of it. Issues of the formation of the principles of democracy and transparency in the activities of trade unions are revealed.